Whale shark residency and small-scale movements around oil and gas platforms in Qatar - Steffen S. Bach; David P. Robinson; Mohammed Y. Al Jaidah; Simon J. Pierce; Prasad Thoppil; Christoph A. Rohner (Frontiers in Marine Science, 2025)
Whale sharks seasonally aggregate near oil and gas platforms in Qatar to feed on fish spawn, creating one of the world’s largest aggregations of the species. We used passive acoustic telemetry to examine their fine-scale movements, residency, and seasonality and investigate whether the platforms influence their space use in this area. Tags had a mean retention of 161 ± 186 days (standard deviation, SD) and 32 of the 117 tags were recorded in multiple years in the acoustic array (21 stations). Most detections were recorded from May to September, confirming that this whale shark aggregation is seasonal. Whale sharks stayed up to 77 consecutive days in the array (mean = 16 ± 12.51 days) and had a mean residency index R max of 0.31. Although most detections (65%) were made at a single receiver located near a platform, here designated P1, an ‘open water’ receiver near this location also had a high proportion of total detections (8.5%). Receivers at other platforms, located away from this specific site, had relatively few detections. The distance from P1, identified as the center of the aggregation, was the main explanatory variable in a GAM. Whale shark aggregations were routinely observed feeding on tuna spawn at the surface at this location, with the eggs (and hence whale sharks) moving with the current through the day, and moving through the array as they did so. Whale sharks then swam against the current in the late afternoon and at night to relocate back to near the presumed tuna spawning site, close to P1, again in the early morning. Rather than being generally associated with platforms, whale sharks were clearly associated with a specific feeding location close to P1. Our results highlight the importance of this small feeding area for whale sharks, which face a high threat level in the region.